ON THE QUASI-REGULARITY OF SPACE TIME TRELLIS CODES ON SLOW FADING CHANNELS - Abou Rajab, Hassan (IEEE, 2013)
In this paper the quasi-regularity property previously introduced by Rouanne and Costello for conventional trellis coded modulation (TCM) schemes is extended to space-time trellis codes (STTC) on slow fading channel for the first time. The minimum determinant and the first higher determinants of the distance matrix together with their multiplicities are computed for some known STTC schemes. The results obtained, indicate that except QPSK, all other PSK signal constellations involve non-regular mappings which necessitates the consideration of all Euclidean distances associated with signal points. The results also indicate that some error events should be taken into account in addition to the one with minimum determinant
10th International Conference on Electronics, Computer and Computation (ICECCO) -- NOV 07-09, 2013 -- Turgut Ozal Univ, Ankara, TURKEY
Keywords: Quasi-regularity; error event; determinant spectrum